A speed estimation-based controller for three-phase AC motors having uncertain parameters - Linh, Lê Hùng; Cát, Phạm Thượng; Tuấn, Phạm Minh (Journal of Computer Science and Cybernetics, 2013)
<!–[if gte mso 9]> <![endif]–> This paper investigates and proposes a three-phase AC motor control system combining an adaptive speed estimation method and control algorithms using neural networks to deal with uncertain parameters in dynamic models of the motor such as the rotor’s resistance, as well as the friction coefficient and load changes when the system operates. Some simulation results on Matlab-Simulink are provided to show the efficiency of the proposed speed estimation and speed control method. <!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; –> <!–[endif] –>